Light scattering, aerosols, clouds, climate, Hendrik van de Hulst, and I. (February 2018) - Chylek, Petr
Highlights: Van de Hulst 2017 Award. His life and mine. What all of us should learn. Abstract: It is not often that I have the opportunity to write something that is not a scientific paper, and I am thankful for this opportunity to express my thoughts with regard to pursuits that are greater than those of science. In this van de Hulst essay, to honor Hendrik van de Hulst, I briefly summarize a few points from Hendrik's life that I find especially interesting, including his interests in spiritual (or religious) aspects of life, and his decision to avoid involvement in nucleation problems, a critical and basic uncertainty of current climate models. After that, I present briefly a few episodes from my own experiences as an apprentice of science and life.